Neotypification, description of nest and plants visited by shorttailed woodstar Myrmia micrura (Gould, 1854) (Revista Científica Ciencias Naturales y Ambientales, 2022)
This paper presents the neotypification, details of the structure of nests, plant parts used in their construction, and a list of plant species visited by the short-tailed hummingbird Myrmia micrura (Gould, 1854).
Keywords: Dry forest; Endemic; Hummingbird; Neotype; Pacifíc